Getting Globalization Right Sustainability and Inclusive Growth in the Post Brexit Age (Springer International Publishing, 2018)
This book presents stimulating new perspectives on three key sets of issues: a fair globalization, the policies that might be adopted in response to protectionist pressures, and sustainable development policies involving G7 and G20 actions to lay the foundations for renewed trust. The individual topics addressed within this framework are wide ranging. Examples include globalization and national inequality, globalization and policies for inclusive growth in developing countries, the sources of controversies regarding trade agreements and their effects, the impact of new U.S. commercial policies on the world trading system, real convergence in the Euro area, and the causes of Brexit. The book comprises a selection of contributions presented at the XXIXth Villa Mondragone International Economic Seminar. In offering contrasting points of view on topics of high current interest, it will appeal to academics, policymakers, and economic experts at institutions. .